The aspartate metabolism pathway - Jonathan, Michael; Sulistyo, Bobby Prabowo (Indonesia International Institute for Life Sciences, 2022)
Recent research has been conducted to find potential new avenues of drug discovery for treating tuberculosis infection. This endless “arms race” is due to the ability of the bacteria to develop resistance towards the already established antibiotic regimen. Various pathways within Mycobacterium tuberculosis are being studied extensively to open new possibilities in drug development. One of which is the aspartate metabolism pathway. This amino acid pathway is proven to be pivotal for the survival of M. tuberculosis both in vitro and in vivo. Furthermore, this pathway also is absent in humans, making it a very promising candidate for further research and development in drug discovery. However, inhibitors against this pathway are not yet available as most suggested inhibitors against the various enzymes within this pathway only made it until the in-silico stage while few studies managed to synthesize their suggested inhibitors and had tested its anti-tuberculosis activity. This review will discuss said attempts in suggesting inhibitors against the critical enzymes that work within this pathway. The inhibitors that are reviewed in this paper are both synthetic and derived from natural products. The multitude of inhibitors proposed and the various enzymes that they are able to inhibit proved that this pathway has potential that is yet to be explored further.